Cytomegalovirus Retinitis in Primary Immune Deficiency Disease - Jia Jeane Ngai; Ka Lung Chong; Shelina Oli Mohamed (Case Reports in Ophthalmological Medicine)
Introduction. To report an unusual case of CMV retinitis in Primary Immune Deficiency Disease (PIDD). Case Report. 13-year-old child with combined T and B cell deficiencies was diagnosed of bilateral zone 1 CMV retinitis. Intravitreal injections were unable to be given in a regular and timely manner under general anaesthesia due to her underlying systemic disease. The child was treated with intravenous ganciclovir for 8 weeks until eventual resolution of the retinitis. However, visual acuity deteriorated due to progressive optic nerve involvement. Conclusion. Paediatric patients often do not notice subtle symptoms of CMV retinitis. Although ocular manifestations are uncommon in PIDD, recognition and high index of suspicion will allow for timely referral, diagnosis, and treatment to be instituted for better visual outcomes.